The relationship of trust, loneliness and social support, and the attitudes towards COVID-19 public health measures - Ćepulić, Dominik-Borna (23rd Psychology Days in Zadar: Book of Selected Proceedings, 2024)
During the COVID-19 pandemic countries implemented public health measures aimed at minimizing social contact. Therefore, the measures have likely altered the quality and the frequency of social relationships, affecting both trust in people and institutions, as well as the sense of loneliness and social support. However, there were contrasting reactions to the implemented measures - some considered them too mild, some too harsh, and others appropriate. This study investigated how these groups of individuals differed in their trust in other people and institutions, as well as in their feeling of loneliness and social support. A Croatian sample of 2115 participants collected at the beginning of the pandemic was examined. The analyses suggested that people who considered measures too mild had lower trust in people, government, and healthcare system than the ones who considered them appropriate. People who considered measures too harsh had lower trust in government, WHO, and were lonelier than people who considered them appropriate. These findings help us elucidate the differences between people with distinct attitudes towards COVID-19 measures in terms of their relationship towards others and the institutions (i.e., trust), and their coping with the challenges of the pandemic (i.e., loneliness and social support).